2018
DOI: 10.1097/bto.0000000000000288
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Blood Flow Restricted Exercise in Hypertension: A Meta-Analysis and Systematic Review With Potential Applications in Orthopedic Care

Abstract: Blood flow restricted (BFR) exercise has recently been promoted in the United States as a novel method to restore skeletal muscle strength and hypertrophy in primarily athletic and healthy populations. A specialized tourniquet restricts blood flow after which brief and intermittent exercise is performed with low to moderate loads of resistance. A hypertensive blood pressure (BP) response during BFR exercise has been identified as a potential adverse effect, which may be particularly concerning for patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
0
19
0
2
Order By: Relevance
“…It has been shown that RT with BFR augmented the strength and cross-sectional area of skeletal muscle [28]. Due to its low load and safety, this is recommended for older people and, in particular, patients with cardiovascular disease, to maintain and improve muscle mass and strength [29]. The pooling data used in this review indicated that the effect of RT with BFR on arterial compliance was better than conventional RT.…”
Section: Arterial Compliancementioning
confidence: 89%
“…It has been shown that RT with BFR augmented the strength and cross-sectional area of skeletal muscle [28]. Due to its low load and safety, this is recommended for older people and, in particular, patients with cardiovascular disease, to maintain and improve muscle mass and strength [29]. The pooling data used in this review indicated that the effect of RT with BFR on arterial compliance was better than conventional RT.…”
Section: Arterial Compliancementioning
confidence: 89%
“…A possible explanation for this positive result is that after the blood flow is released from the training muscle, the reperfusion process of locally and rapidly congested blood induces the release of endothelium-dependent vasodilator, resulting in an increase in local blood flow, thereby reducing vascular resistance and blood pressure [ 27 , 28 ]. Given that BFR training is conducive to reducing cardiac preload during training, some studies have shown that it can be used as a more effective exercise intervention in hypertensive patients [ 29 , 30 ]. However, in contrast with the results of meta-analyses conducted by previous researchers [ 31 ], in this study we noted that, while LL-BFR had a better hypotensive effect than the conventional LL-RT or HL-RT training, there was no statistically significant difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…hypertensive subjects) 28,29 . However, some studies have indicated that exercise with BFR exercise seems to be safe in hypertensive subjects because they did not present any adverse events [30][31][32] . Furthermore, the acute effect during exercise with BFR slightly increases SBP 30 , whereas the chronic effect decreases SBP in hypertensive subjects 31 .…”
Section: Discussionmentioning
confidence: 99%